Playing with Vieta

Algebra Level 5

x 4 + 37 x 3 + 71 x 2 + 18 x + 3 \large x^4 + 37x^3 + 71x^2 + 18x + 3

If a a , b b , c c , and d d represent the roots of the polynomial above, find the sum of the coefficients of the monic polynomial whose roots are a b c d \large\frac{abc}{d} , a b d c \large \frac{abd}{c} , a c d b \large\frac{acd}{b} , and b c d a \large\frac{bcd}{a} .

Inspiration .


The answer is 78.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ayush Verma
Jul 3, 2015

f ( x ) = x 4 + 37 x 3 + 71 x 2 + 18 x + 3 s u m o f c o e f f . o f h ( x ) = h ( 1 ) h ( 1 ) = ( 1 a b c d d 2 ) ( 1 a b c d c 2 ) ( 1 a b c d b 2 ) ( 1 a b c d a 2 ) = ( d 2 3 d 2 ) ( c 2 3 c 2 ) ( b 2 3 b 2 ) ( a 2 3 a 2 ) ( a s a b c d = 3 ) = ( d 2 3 ) ( c 2 3 ) ( b 2 3 ) ( a 2 3 ) 9 ( a s a 2 b 2 c 2 d 2 = 9 ) = f ( 3 ) . f ( 3 ) 9 ( ( a 2 3 ) = ( 3 a ) ( 3 a ) ) = ( 225 + 129 3 ) ( 225 129 3 ) 9 = 78 f\left( x \right) ={ x }^{ 4 }+37{ x }^{ 3 }+71{ x }^{ 2 }+18x+3\\ \\ sum\quad of\quad coeff.\quad of\quad h\left( x \right) =h\left( 1 \right) \\ \\ h\left( 1 \right) =\left( 1-\cfrac { abcd }{ { d }^{ 2 } } \right) \left( 1-\cfrac { abcd }{ { c }^{ 2 } } \right) \left( 1-\cfrac { abcd }{ { b }^{ 2 } } \right) \left( 1-\cfrac { abcd }{ { a }^{ 2 } } \right) \\ \\ =\left( \cfrac { { d }^{ 2 }-3 }{ { d }^{ 2 } } \right) \left( \cfrac { { c }^{ 2 }-3 }{ { c }^{ 2 } } \right) \left( \cfrac { { b }^{ 2 }-3 }{ { b }^{ 2 } } \right) \left( \cfrac { { a }^{ 2 }-3 }{ { a }^{ 2 } } \right) \quad (as\quad abcd=3)\\ \\ =\cfrac { \left( { d }^{ 2 }-3 \right) \left( { c }^{ 2 }-3 \right) \left( { b }^{ 2 }-3 \right) \left( { a }^{ 2 }-3 \right) }{ 9 } \quad (as\quad { a }^{ 2 }{ b }^{ 2 }{ c }^{ 2 }{ d }^{ 2 }=9)\\ \\ =\cfrac { f\left( \sqrt { 3 } \right) .f\left( -\sqrt { 3 } \right) }{ 9 } \quad (\because \left( { a }^{ 2 }-3 \right) =\left( \sqrt { 3 } -a \right) \left( -\sqrt { 3 } -a \right) )\\ \\ =\cfrac { \left( 225+129\sqrt { 3 } \right) \left( 225-129\sqrt { 3 } \right) }{ 9 } =78

WOW MARVELOUS!

Pi Han Goh - 5 years, 11 months ago
汶良 林
Jun 26, 2015

Would you explain how you went from the step with degree 4 4 equation to the step with degree 8 8 equation?

Prasun Biswas - 5 years, 11 months ago

Log in to reply

(x^4 + 71x^2 + 3)^2 = (-37x^3 - 18x)^2

汶良 林 - 5 years, 11 months ago

Log in to reply

Ah, I see. You squared both sides.

Prasun Biswas - 5 years, 11 months ago

Substituted x = sqrt (3/y) instead. Did it by the same way.

Devin Ky - 5 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...